DEVELOPMENT OF PUBLIC FOUNTAINS SYSTEM IN THE TERRITORY OF THE CITY OF BELGRADE AS A RESPONSE TO ADAPTATION TO HEAT WAVES - Spasojevic, Nenad; Šabanović, Ana; Filipović, Lazar (Political Review, 2025)
In this Paper, the authors examine the current state of coverage of public fountains in the urban area of the city of Belgrade. There are over 200 public fountains in Belgrade, where water is either spring-sourced or supplied from the city water supply. Due to the consequences of climate change and increasingly high temperatures, public fountains are becoming increasingly important for citizens. As adaptation measures to the consequences of climate change, these facilities represent an advantageous way to respond to newly emerging challenges. However, in the territory of the city of Belgrade, the current number of public fountains is not sufficient to respond to existing challenges, and at the same time, their territorial representation is not fully adequate. The applied research methodology in the Paper includes mapping public fountains and comparing their spatial distribution to the areas of the city with the highest average number of days with maximum daily temperature exceeding 30°C in the urban area of Belgrade to identify the most vulnerable zones. The analysis shows that there is a possibility of installing public fountains in open spaces in areas of public use for education and primary health care, as well as in parks. Attention should also be paid to the most vulnerable zones, such as business, industrial, and brownfield zones, i.e., zones under large-scale buildings with extensive accompanying transport infrastructure, which also lack public fountain coverage. The potential installation of new public fountains on the territory of the city of Belgrade would provide citizens with greater access to drinking water. Existing and new public fountains would not solve the problems of climate change, but they would certainly improve adaptation.
Keywords: public fountains; adaptation; heat waves; climate change; Belgrade